2017
DOI: 10.1016/s1470-2045(17)30104-3
|View full text |Cite
|
Sign up to set email alerts
|

Nivolumab for previously treated unresectable metastatic anal cancer (NCI9673): a multicentre, single-arm, phase 2 study

Abstract: Summary Background Squamous cell carcinoma of the anal canal (SCCA) is a rare malignancy associated with infection by human papillomavirus (HPV). No consensus treatment approach exists for the treatment of metastatic disease. Because intratumoral HPV oncoproteins upregulate immune checkpoint proteins such as PD-1 to evade immune-mediated cytotoxicity, we did a trial of the anti-PD-1 antibody nivolumab for patients with metastatic SCCA. Methods We did this single-arm, multicentre, phase 2 trial at ten academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
242
1
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 343 publications
(273 citation statements)
references
References 33 publications
3
242
1
9
Order By: Relevance
“…Ultimately, in describing the tumor microenvironment, we hoped to gain insight into potential avenues for therapeutic intervention that may improve outcomes for the subset of patients who are not cured by upfront chemoradiation. A phase II study of nivolumab in metastatic ASCC showed a 24% response rate to anti‐PD‐1‐directed therapy, which serves as proof of principle that immunotherapy can have an important role in this disease . Responders were found to have higher CD8, PD‐1, and PD‐L1 levels.…”
Section: Discussionmentioning
confidence: 94%
“…Ultimately, in describing the tumor microenvironment, we hoped to gain insight into potential avenues for therapeutic intervention that may improve outcomes for the subset of patients who are not cured by upfront chemoradiation. A phase II study of nivolumab in metastatic ASCC showed a 24% response rate to anti‐PD‐1‐directed therapy, which serves as proof of principle that immunotherapy can have an important role in this disease . Responders were found to have higher CD8, PD‐1, and PD‐L1 levels.…”
Section: Discussionmentioning
confidence: 94%
“…One phase II study investigated nivolumab in metastasized anal cancer and showed a response in 24% of patients. The response was dependent on PD-L1 expression [58]. Disappointing results came from investigations which aimed to introduce immuno-oncological approaches to the treatment of pancreatic cancer [59].…”
Section: Other Gi Cancer Typesmentioning
confidence: 99%
“…V jednoramenné klinické studii fáze II byl testován nivolumab u pa cientů s metastatickým análním karcinomem, kteří byli refrakterní na běžnou systémovou chemoterapii. Do studie bylo zařazeno 37 pa cientů a byly zaznamenány 2 CR a 7 PR -ORR 24 % (95% CI 15-33) [12]. Podobně příz-nivé výsledky byly zaznamenány ve studii KEYNOTE-028 s pembrolizumabem, kdy u obdobné skupiny pa cientů se spinocelulárním karcinomem anu byl ORR 17 % (95% CI 5-37), kontroly onemocnění bylo dosaženo u 58 % [13].…”
Section: Imunoterapie V Léčbě Karcinom Anuunclassified